Lithium-based ceramic material and preparation method thereof

By using two crucibles and pre-firing powder during the lithium-based ceramic sintering process, the concentration of lithium elements is adjusted, the problem of pore formation is solved, and the high-density lithium-based ceramic material is achieved, which improves its conductivity and stability. sex.

CN119430933APending Publication Date: 2025-02-14JIANGSU XINLIYUAN TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411680835.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing lithium-based ceramic materials are prone to pores during sintering, which affects their density and leads to poor ionic conductivity and stability.

Method used

By using two crucibles and pre-fired powder to combine during the sintering process, the concentration of lithium elements is adjusted, and the formation of pores is reduced, thereby increasing the density of ceramic materials.

Benefits of technology

It is achieved to obtain a high density of lithium-based ceramic materials under normal pressure, with a density of 95% to 99%, which improves the ionic conductivity of the material and the stability to lithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430933A_ABST
    Figure CN119430933A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-based ceramic material and a preparation method thereof.The method comprises the following steps that S1, a plurality of lithium-based ceramic green bodies are stacked in the thickness direction and placed in a first crucible with first lithium-based ceramic pre-sintered powder laid at the bottom, and second lithium-based ceramic pre-sintered powder is scattered among the multiple lithium-based ceramic green bodies; s2, a second crucible with an opening facing downwards is inversely buckled into the first crucible, and the multiple lithium-based ceramic green bodies are contained in the second crucible; s3, the first crucible containing the second crucible is sealed through a crucible cover and then sintered, the lithium-based ceramic green body is sintered, and the lithium-based ceramic material is obtained. According to the method, the lithium-based ceramic material with relatively high density can be obtained under normal pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium-based ceramic production, and specifically relates to a lithium-based ceramic material and a preparation method thereof. Background Art

[0002] Currently, commercial lithium-ion batteries mainly use organic electrolytes, which have safety hazards such as leakage, combustion, and explosion in unconventional environments. Solid-state batteries based on inorganic solid ceramic electrolytes are of great significance in solving the safety problems of traditional liquid batteries. In addition, solid-state lithium batteries have the advantages of high specific energy, long cycle life, low self-discharge and strong designability. They have been widely used in fields such as microelectronic systems and portable electronic devices. The key to the development of solid-state batteries lies in the research and development of high-performance solid electrolytes. Lithium-based ceramics represented by garnet-type (LLZO) solid electrolytes have high ionic conductivity and are stable to lithium metal. They are one of the most popular solid electrolyte materials at present. They can be used in all-solid-state batteries and lithium extraction, and have strong application prospects.

[0003] Related technologies mainly study the doping and structure of this type of ceramics. Metal cations such as Al, Ga, Nb, and Ta are tried to be doped into the LLZO lattice to stabilize its cubic phase and improve its conductivity; the structural analysis of the tetragonal and cubic phases, the location of lithium ions, and the understanding of its lithium ion transport channels. However, the sintering mechanism of this type of ceramics and the corresponding process optimization are rarely reported.

[0004] The density of lithium-based ceramic materials has a great influence on their ionic conductivity and stability, so it is necessary to improve the density of lithium-based ceramic materials. Summary of the invention

[0005] In view of this, the present application provides a lithium-based ceramic material and a preparation method thereof, aiming to provide a method for preparing a lithium-based ceramic material with higher density and a high-density lithium-based ceramic material.

[0006] In a first aspect, the present application provides a method for preparing a lithium-based ceramic material, comprising the following steps:

[0007] Step S1: stacking a plurality of lithium-based ceramic green sheets in a thickness direction and placing them in a first crucible with a first lithium-based ceramic pre-fired powder on the bottom, wherein a second lithium-based ceramic pre-fired powder is sprinkled between the plurality of lithium-based ceramic green sheets;

[0008] Step S2: placing the second crucible upside down into the first crucible with its opening facing downward, so that the plurality of lithium-based ceramic green sheets are contained in the second crucible;

[0009] Step S3: sealing the first crucible containing the second crucible with a crucible cover and then performing a sintering process to sinter the lithium-based ceramic green body to obtain the lithium-based ceramic material.

[0010] Based on the present application, since lithium element will volatilize at high temperature, lithium element is supplemented by excess lithium source, but the degree of excess lithium source cannot be accurately controlled in the actual process, and the excess is usually greater. Therefore, when the lithium source is more excessive, the lithium excess inside the green body will also be more, resulting in more pores during the sintering process, which in turn affects the density of the ceramic body. Therefore, the present application solves the problem of multiple pores caused by excessive lithium source by combining external and internal lithium element supplementation during the sintering process, that is, by setting pre-burned powder in combination with the first crucible and the second crucible, and jointly adjusting the Li element concentration in the atmosphere during the sintering process with the lithium element escaping from the green body, the effect of replenishing lithium and eliminating pores is achieved.

[0011] Specifically, laying the first lithium-based ceramic pre-fired powder on the bottom of the first crucible and sealing it with a crucible cover can effectively increase the concentration of lithium elements inside the first crucible, thereby replenishing the lithium elements lost by the lithium-based ceramic green body during the sintering process; at the same time, the second crucible is turned upside down into the first crucible so that the lithium-based ceramic green body is accommodated in the second crucible, which can further reduce the volume of the space where the lithium-based ceramic green body is located, and the lithium elements volatilized by the lithium-based ceramic green body during the sintering process are fixed to the space of the second crucible, and the first lithium-based ceramic pre-fired powder laid on the bottom makes the lithium concentration in the space of the second crucible higher; in addition, a plurality of lithium-based ceramic green bodies are stacked, and the concentration of lithium elements in the space of the second crucible gradually increases from bottom to top, so that the lithium elements volatilized by the lithium-based ceramic green body located in the upper layer during the sintering process are more easily replenished, so that the density of the sintered lithium-based ceramic material gradually increases from bottom to top, thereby the above method can obtain a lithium-based ceramic material with a higher density under normal pressure.

[0012] In some embodiments, the height h of the plurality of lithium-based ceramic green sheets stacked in the thickness direction and the height H of the second crucible satisfy 0.3H≤h<H, preferably 0.5H≤h<H; further preferably 0.7H≤h<H; and further preferably 0.9H≤h<H.

[0013] In some of the above embodiments, since the density of the lithium-based ceramic material prepared by this method gradually increases from bottom to top, the higher the stacking height in the second crucible, the higher the density of the lithium-based ceramic material on the upper layer. When h and H meet the above conditions, it is easier to obtain a high-density lithium-based ceramic material.

[0014] When the total height satisfies 0.3H≤h<H, some lithium-based ceramic materials with a density of 95% to 96% or above can be obtained; when the total height satisfies 0.5H≤h<H, some lithium-based ceramic materials with a density of 96% to 97% or above can be obtained; when the total height satisfies 0.7H≤h<H, some lithium-based ceramic materials with a density of 97% to 99% or above can be obtained; when the total height satisfies 0.9H≤h<H, some lithium-based ceramic materials with a density of 99% or above can be obtained.

[0015] In some examples, when the total height satisfies 0.3H≤h<0.5H, a portion of ceramic material with a density of 95% to 96% can be obtained (usually the ceramic sheet located at the upper part); in some examples, when the total height satisfies 0.5H≤h<0.7H, a portion of ceramic material with a density of 96% to 97% can be obtained (usually the ceramic sheet located at the upper part); in some examples, when the total height satisfies 0.7H≤h<0.9H, a portion of ceramic material with a density of 97% to 99% can be obtained (usually the ceramic sheet located at the upper part); in some examples, when the total height satisfies 0.9H≤h<H, a portion of ceramic material with a density of 99% or above can be obtained (usually the ceramic sheet located at the upper part).

[0016] In the present application, by controlling the total height of the green sheets stacked in the second crucible so that the total height gradually increases, the corresponding density of the green sheets at the upper part (usually the top layer or layers) can also become higher and higher. Therefore, when a high-density ceramic material is needed, the technicians in this field can control the total height of the stack according to the corresponding relationship between the total height and the density taught in the present application, and obtain the lithium-based ceramic material with the required density.

[0017] In some embodiments, the height of the second crucible is 45 to 50 mm, the thickness of the lithium-based ceramic green body is 3.2 to 3.7 mm, and the number of lithium-based ceramic green bodies in the second crucible can be more than 4. Based on the above method, the density of the lithium-based ceramic sheet located on the upper layer is higher. Of course, the height of the second crucible itself and the thickness of the lithium-based ceramic green body in the present application can also be other parameter ranges.

[0018] In some embodiments, the total height h of the plurality of lithium-based ceramic green sheets stacked in the thickness direction and the height H of the second crucible satisfy: 0.5H≤h<H; and, when the height h1 of a certain lithium-based ceramic green sheet after the plurality of lithium-based ceramic green sheets are stacked satisfies 0.3H≤h1<0.7H, the density of the ceramic material obtained by sintering the green sheet is 96%-97%; when the height h1 of a certain lithium-based ceramic green sheet after the plurality of lithium-based ceramic green sheets are stacked satisfies 0.7H≤h1<0.9H, the density of the ceramic material obtained by sintering the green sheet is 97%-99%; when the height h1 of a certain lithium-based ceramic green sheet after the plurality of lithium-based ceramic green sheets are stacked satisfies 0.9H≤h1<H, the density of the ceramic material obtained by sintering the green sheet is greater than or equal to 99%; wherein, the height h1 is the distance between the upper surface of a certain lithium-based ceramic green sheet and the lower surface of the lowest lithium-based ceramic green sheet.

[0019] Specifically, in the present application, when the total stacking height of the lithium-based ceramic green sheets reaches 0.5H or more, for different total heights, for a lithium-based ceramic green sheet with the same or similar height, the density of the ceramic sheet obtained by sintering is not much. For example, when 8 green sheets are stacked and 12 green sheets are stacked, for lithium-based ceramic green sheets within the range of 0.3H≤h1<0.7H, the density of the ceramic sheet obtained by sintering is within 96% to 97%; when the height h1 of the ceramic green sheet can reach 0.7H≤h1<0.9H, the density of the ceramic sheet obtained by sintering can continue to increase to 97% to 99%; similarly, when the height h1 of the ceramic green sheet can reach 0.9H≤h1<H, the density of the ceramic sheet obtained by sintering can continue to increase to 99% and above. That is to say, when the total height reaches above 0.5H, the relationship between the density of the ceramic sheet obtained by sintering the green body and the total height h seems to be weakening, and is related to the height h1 at which it is located.

[0020] This seems to be different from the case where the total thickness of the stack is less than 0.5H. When the total height of the stacking and firing is less than 0.5H, the density of the ceramic sheet obtained by sintering a lithium-based ceramic green body with the same or similar height h1 varies relatively greatly. For example, when sintering is performed by stacking 4 green bodies and stacking 8 green bodies, the density of the ceramic sheet obtained by sintering is different for lithium-based ceramic green bodies in the range of 0.3H≤h1<0.7H. According to experimental research, for the scheme of stacking 4 green bodies, the density of the ceramic sheet obtained by sintering lithium-based ceramic green bodies in the range of 0.3H≤h1<0.5H is less than the density of the ceramic of the same height corresponding to the scheme of 8 green bodies. In other words, when the total height h is less than 0.5H, the density of the ceramic sheet obtained by sintering the green body seems to be relatively related to the total height h, and of course it is also related to its own height h1.

[0021] Therefore, the method provided in the present application can more accurately control the density of the ceramic material obtained by sintering each layer of lithium-based ceramic green body when the total height is controlled to be above 0.5H. Of course, this requires considering the height h1 of each layer of lithium-based ceramic green body at the same time, that is, by placing them at different heights h1, ceramic materials of different densities can be quantitatively obtained to meet different needs.

[0022] In some embodiments, the particle size of the first lithium-based ceramic pre-fired powder is 0.5 to 5 mm; the particle size of the second lithium-based ceramic pre-fired powder is 20 to 80 μm.

[0023] In some of the above embodiments, the first lithium-based ceramic pre-burned powder is laid on the bottom of the first crucible, and its main function is to increase the lithium concentration in the space between the first crucible and the second crucible, and the particle size of the first lithium-based ceramic pre-burned powder is controlled to be 0.5-5 mm. At this time, on the one hand, when the first lithium-based ceramic pre-burned powder layer is laid on the bottom of the first crucible, the porosity of the first lithium-based ceramic pre-burned powder layer is relatively high, and the lithium volatilized from the pre-burned powder at the bottom is more easily dissipated, thereby further increasing the lithium concentration in the space of the second crucible; on the other hand, the first lithium-based ceramic pre-burned powder can be reduced from being sintered at the bottom of the first crucible. The second lithium-based ceramic pre-fired powder is arranged between several lithium-based ceramic green bodies, and its main function is to reduce the sintering of adjacent lithium-based ceramic green bodies, and the particle size of the first lithium-based ceramic pre-fired powder is controlled at 20-80 μm, which is conducive to the more stable stacking of lithium-based ceramic green bodies. At the same time, more lithium-based ceramic green bodies can be stacked at the same stacking height, and the lithium element in the lithium-based ceramic pre-fired powder is more easily volatilized at this time, thereby further increasing the lithium concentration in the second crucible space, thereby further improving the density of the upper lithium-based ceramic sheet.

[0024] In some embodiments, the step S1 further comprises: after laying a layer of second lithium-based ceramic pre-fired powder on the first lithium-based ceramic pre-fired powder, stacking a plurality of lithium-based ceramic green sheets along the thickness direction and placing them on the second lithium-based ceramic pre-fired powder.

[0025] In some of the above-mentioned embodiments, a layer of second lithium-based ceramic pre-fired powder is laid on the bottom layer of lithium-based ceramic green body and the first lithium-based ceramic pre-fired powder. The small-particle size of the second lithium-based ceramic pre-fired powder is conducive to the stacking of lithium-based ceramic green body. In addition, since the porosity of the first lithium-based ceramic pre-fired powder is relatively large, laying a layer of second lithium-based ceramic pre-fired powder with small particle size on it is conducive to improving the sealing of the second crucible, reducing the transfer of lithium elements in the second crucible space through the gap to the outside, and further increasing the concentration of lithium elements in the second crucible space, thereby further improving the density of the lithium-based ceramic sheet.

[0026] In some embodiments, the first crucible, the second crucible and the crucible cover are all made of magnesium oxide. Based on the above embodiments, the aluminum ions in the traditional alumina crucible can be prevented from being conducted through the crucible to the ceramic pre-fired powder. The aluminum ions can replace the position of lithium ions in the ceramic pre-fired powder and cause pollution to the lithium-based ceramics. Therefore, the use of magnesium oxide crucibles can reduce impurities in lithium-based ceramic materials; at the same time, MgO does not react with lithium atmosphere, which can reduce the amount of buried powder, increase the concentration of lithium elements in the space, and further improve the density of lithium-based ceramic materials.

[0027] In some embodiments, the first lithium-based ceramic pre-fired powder and the second lithium-based ceramic pre-fired powder are independently obtained by the following method: providing raw materials according to the stoichiometric ratio of each element in the lithium-based ceramic material, wherein the raw materials include a lithium source, the mass of the lithium element in the lithium source is recorded as m, the theoretical amount of lithium element is recorded as m0, and 1.1m0≤m≤1.2m0 is satisfied; and then the raw materials are pre-fired and crushed at 800-1000°C to obtain the lithium-based ceramic pre-fired powder. Based on the above embodiment, the first lithium-based ceramic pre-fired powder and the second lithium-based ceramic pre-fired powder can effectively increase the concentration of lithium elements in the space of the first crucible and the second crucible, thereby further improving the density of the lithium-based ceramic material.

[0028] In some embodiments, the lithium-based ceramic green body is obtained by the following method: providing raw materials according to the stoichiometric ratio of each element in the lithium-based ceramic material, wherein the raw materials include a lithium source, the mass of the lithium element in the lithium source is recorded as m, the theoretical amount of lithium element is recorded as m0, and 1.1m0≤m≤1.2m0 is satisfied; the raw materials are then pre-fired and crushed at 800-1000°C to obtain lithium-based ceramic pre-fired powder; and then the lithium-based ceramic pre-fired powder is granulated and formed to obtain the lithium-based ceramic green body. Based on the above embodiment, the lithium element volatilized in the lithium-based ceramic green body during the sintering process can be transferred and supplemented between layers, thereby further improving the density of the lithium-based ceramic material.

[0029] In some embodiments, the sintering treatment conditions include: heating to 1000-1100° C. at a rate of 3-5° C. / min and maintaining the temperature for 3-7 hours.

[0030] In some embodiments, the lithium-based ceramic material is selected from any one of the substances represented by Formula 1;

[0031] Li 7-x Ln3Z 2-x M x O 12 Formula 1

[0032] Wherein, M is a doping element, and M is selected from at least one of Ta, Nb, W, and Ti; the value range of x is: 0≤x≤1.0.

[0033] In some of the above embodiments, the lithium-based ceramic satisfying the above formula 1 is a LLZO-based solid electrolyte, which has high ionic conductivity, stable structure and strength, and can be used as a solid electrolyte in a battery; at the same time, by doping the M element in the Zr position, the LLZO-based solid electrolyte can maintain a cubic phase at room temperature, and the LLZO-based solid electrolyte has a higher ionic conductivity than the tetragonal phase.

[0034] In some embodiments, the raw materials further include a La source, a Zr source, and a doping element M source.

[0035] In some embodiments, the Li source includes at least one of lithium carbonate, lithium nitrate, and lithium hydroxide, preferably lithium carbonate.

[0036] In some embodiments, the La source includes at least one of lanthanum oxide, lanthanum hydroxide, and lanthanum nitrate, preferably lanthanum hydroxide.

[0037] In some embodiments, the Zr source includes at least one of zirconium oxide, zirconium hydroxide, and zirconium nitrate, preferably zirconium oxide.

[0038] In some embodiments, the doping element M source is a Ta source, and the Ta source includes one of tantalum oxide, tantalum hydroxide, and tantalum nitrate, preferably tantalum oxide.

[0039] In the present application, the method for preparing lithium-based ceramic materials also includes providing raw materials according to the stoichiometric ratio of lithium-based ceramics, and then obtaining lithium-based ceramic materials through mixing, pre-firing, spray granulation, molding, sintering and other steps.

[0040] In a second aspect, the present application provides a lithium-based ceramic material prepared according to the method described in any embodiment of the first aspect.

[0041] Based on the present application, since the lithium-based ceramic material is prepared according to the method described in any embodiment of the first aspect, it has the beneficial effect of the first aspect, that is, it has a higher density.

[0042] In some embodiments, the density of the lithium-based ceramic material is greater than 96%. Based on the above embodiments, the lithium-based ceramic material has better ionic conductivity and stability to lithium. Preferably, the density of the lithium-based ceramic material is greater than 97%; further preferably, the density of the lithium-based ceramic material is greater than 99%.

[0043] In the present application, the pre-burning process may be any suitable method in the prior art, or the following method provided in the present application:

[0044] A method for preparing lithium-based ceramic pre-sintered powder comprises the following steps:

[0045] Step S1: providing raw materials according to the stoichiometric ratio of lithium-based ceramics;

[0046] Step S2: mixing the raw materials with an alcohol solvent and grinding them to obtain a slurry;

[0047] Step S3: directly pre-sintering the slurry after drying to obtain lithium-based ceramic pre-sintered powder.

[0048] In some embodiments, in step S2, the alcohol solvent includes at least one of methanol, ethanol, and propanol;

[0049] The mass ratio of the raw material to the alcohol solvent is 0.2-0.7:1.

[0050] In some implementations, in step S2, the Dv50 of the raw materials in the slurry is below 0.5 μm.

[0051] In some embodiments, in step S3, directly pre-firing the slurry after drying it comprises: placing the slurry in a magnesium oxide crucible, drying it, and then directly pre-firing it;

[0052] Preferably, the drying conditions include: drying temperature: 70°C to 90°C; drying time: 600min to 800min.

[0053] In some implementations, in step S3, the liquid level of the slurry in the magnesium oxide crucible does not exceed 10 mm.

[0054] In some embodiments, in step S3, the pre-sintering treatment conditions include: heating to 390-410°C and keeping warm for 60-550 minutes, then heating to 640-660°C and keeping warm for 60-550 minutes, then heating to 710-730°C and keeping warm for 60-550 minutes, then heating to 760-770°C and keeping warm for 60-550 minutes, then heating to 910-930°C and keeping warm for 300 minutes. Preferably, in step S3, the pre-firing treatment conditions include: heating to 390-410°C and keeping warm for 120-480min, then heating to 640-660°C and keeping warm for 120-480min, then heating to 710-730°C and keeping warm for 120-480min, then heating to 760-770°C and keeping warm for 120-480min, then heating to 910-930°C and keeping warm for 300-600min.

[0055] In some embodiments, the heating rates in the pre-calcination treatment are independently 3 to 10° C. / min.

[0056] In the present application, the spray granulation may be any suitable method in the prior art, or the following method provided in the present application:

[0057] A method for preparing lithium-based ceramic granulated powder comprises the following steps:

[0058] Step S1: providing raw material powder according to the stoichiometric ratio of lithium-based ceramics, and pre-sintering to obtain lithium-based ceramic pre-sintered powder, wherein the raw material powder includes a lithium source;

[0059] Step S2: mixing the lithium-based ceramic pre-sintered powder with a composite solvent to prepare a slurry, wherein the composite solvent includes an organic solvent and water;

[0060] Step S3: subjecting the slurry to a spray granulation process to obtain lithium-based ceramic granulated powder.

[0061] In some embodiments, in step S2, the organic solvent includes at least one of ethanol, propanol, and n-butanol; preferably, the organic solvent is ethanol.

[0062] In some implementations, in step S2, in the composite solvent, the mass ratio of the organic solvent to water is 1:2-5; preferably, the mass ratio of the organic solvent to water is 1:2.5-3.

[0063] In some implementations, in step S2, the solid content of the slurry is 20 wt% to 70 wt%.

[0064] In some implementations, in step S2, the pH of the slurry is 8-10.

[0065] In some embodiments, in step S3, the conditions of the spray granulation treatment include: an air inlet temperature of 130-160°C; preferably, the air inlet temperature is 145-155°C.

[0066] In some embodiments, in step S3, the conditions of the spray granulation treatment further include: introducing a gas into the air inlet, wherein the gas includes an inert gas;

[0067] Preferably, the gas also includes air;

[0068] Preferably, the volume ratio of the inert gas to air is 1:3-7;

[0069] Further preferably, the volume ratio of the inert gas to air is 1:4.5-5.5.

[0070] Compared with the prior art, the beneficial effects of the present application are at least:

[0071] (1) The experimental conditions required by the method provided in this application are not high. By sintering under normal pressure, lithium-based ceramic materials with different densities can be obtained to meet different requirements. The density of the obtained lithium-based ceramic materials can reach 95% to 99%;

[0072] (2) During the sintering process of lithium-based ceramic green bodies, the high-concentration lithium in the small space provided by the two crucibles and the pre-burned powder becomes part of the lithium in the sintering atmosphere. At the same time, the green body itself also provides part of the lithium in the sintering atmosphere, because the lithium in the green body itself will volatilize during the sintering process. That is, the green body itself relies on lithium supplementation, which can improve the density, reduce the total amount of buried powder, and reduce production costs;

[0073] (3) In the method provided by the present application, the first crucible and the second crucible and the pre-burned powder are arranged, and the pre-burned powder is laid on the bottom of the first crucible to achieve the effect of initial lithium supplementation, and then the second crucible is further used to further reduce the volume inside the crucible and increase the lithium concentration, and the stacking method is used to cooperate with the high Li concentration in the atmosphere to obtain a high-density ceramic body and reduce the cost;

[0074] (4) The method provided by this process is that as the height (i.e., quantity) of the green body increases, it will provide more lithium atmosphere (evaporated from itself), relying on the lithium of the green body itself to supplement each other. The Li concentration in the atmosphere increases as you move up (this is mainly because lithium oxide will sublimate into gas and gather upwards), and there are no other factors affecting it. Therefore, the density of the ceramic body increases as you move up, and the top layer or layers can reach a density of 99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 This is a schematic diagram of the device of Example 1 of the present application.

[0076] Figure 2 This is a schematic diagram of the device of Example 3 of the present application.

[0077] Figure 3 This is a schematic diagram of the device of comparative example 1 of the present application.

[0078] Figure 4 This is a density distribution diagram of each LLZTO ceramic sheet in Examples 1 and 3 and Comparative Example 1 of the present application.

[0079] Among them, 1-lithium-based ceramic green body, 2-first lithium-based ceramic pre-fired powder, 3-first crucible, 4-second lithium-based ceramic pre-fired powder, 5-second crucible, 6-crucible cover. DETAILED DESCRIPTION

[0080] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0081] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.

[0082] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0083] Lithium-based ceramics (such as LLZO or LLZTO, etc.) contain a large amount of alkali metal lithium (29 mol%). During the sintering process, there are two problems: volatilization of alkali metal elements and excessive grain growth, which makes it difficult to densify. In the published work, complex and expensive hot pressing, plasma sintering and field-assisted hot pressing are used to sinter lithium-based ceramics to obtain high-density (>97%) ceramics. However, it is difficult to obtain ceramics with a density of more than 95% using low-cost atmospheric pressure sintering methods, which requires further exploration and research.

[0084] The present application proposes a method for sintering lithium-based ceramics at high density at normal pressure. The method adopts a solid phase reaction method at normal pressure, granulates and shapes lithium-based ceramic pre-sintered powder to obtain defect-free green bodies, and then sinters according to the following sintering method to obtain ultra-high density lithium-based ceramic sheets. Therefore, the technical solution of the present invention will contribute to the development and application of solid-state lithium-ion batteries.

[0085] This application proposes a technical solution for the normal pressure high-density sintering of lithium-based ceramic sheets, which is achieved by the following methods:

[0086] First, this technical solution requires the use of lithium-based ceramic pre-sintered powder prepared at 800°C to 1000°C and lithium-based ceramic granulated powder (10-20% excess Li, the lithium in the green body will volatilize during sintering, so the lithium-based ceramic green body needs to have excess lithium) for pressing the green body after a series of processes such as pre-sintering, sand grinding, and spray granulation.

[0087] The sintering method of this scheme is as follows Figure 1 As shown, the first crucible 3, the second crucible 5 and the crucible cover 6 are all made of MgO material (MgO crucible does not react with lithium atmosphere, which can reduce the amount of buried powder, while the commonly used alumina and zirconia crucibles on the market will absorb lithium atmosphere), the crucible cover 6 is flat, the first crucible 3 and the second crucible 5 are cylindrical, and a plurality of lithium-based ceramic green bodies 1 are stacked along the thickness direction and placed in the first crucible 3 with the first lithium-based ceramic pre-burned powder 2 laid on the bottom. In the figure, the first lithium-based ceramic pre-burned powder 2 and the second lithium-based ceramic pre-burned powder 4 are both lithium-based ceramic pre-burned powders prepared at 800°C to 1000°C, the second lithium-based ceramic pre-burned powder 4 represents a finer powder that has been ground and sieved, and the first lithium-based ceramic pre-burned powder 2 is a large-particle powder.

[0088] 1. A large-particle first lithium-based ceramic pre-burned powder 2 is spread on the bottom of a larger MgO crucible 3 as buried powder to compensate for the volatilization of Li in the space. This is because the lithium-based ceramic green body needs to have an excess of lithium inside. When the excess of Li inside is too much, it will cause more pores inside the ceramic sheet, so it is compensated from the outside by burying powder;

[0089] 2. Evenly sprinkle a layer of ground and sieved second lithium-based ceramic pre-burned powder 4 on the top layer of the first lithium-based ceramic pre-burned powder 2 to ensure that the green body can be in full and smooth contact with the buried powder;

[0090] 3. Arrange and compact the green body, fine pre-burned powder and green body in an orderly manner;

[0091] 4. The smaller MgO crucible 5 is inverted and covered with the top MgO cover 6. The purpose of inverting the smaller MgO crucible 5 is to reduce the space where the green body is located as much as possible and increase the concentration of lithium atmosphere. The MgO cover 6 plays an overall sealing role to prevent the internal lithium atmosphere from overflowing and affecting sintering and damaging the furnace;

[0092] 5. Place it in a box furnace and raise the temperature to 1100℃ at 3-5℃ / min and keep it for 5 hours for sintering.

[0093] 6. In an example of the present application, when a smaller MgO crucible 5 is inverted, the overall density of the lithium-based ceramic sheet can be significantly improved from 94-95% to about 95-99%.

[0094] 7. Further, when the total height h of the stacked lithium-based ceramic green bodies and the height H of the small MgO crucible satisfy h / H≥0.5, and the height h1 of each layer of the stacked LLZTO green bodies and the height H of the small MgO crucible;

[0095] When h1≥30%H is satisfied, the density of the ceramic sheet obtained by sintering the green body of this layer and the green bodies above this layer is more than 96%;

[0096] When h1≥70%H is satisfied, the density of the ceramic sheet obtained by sintering the green body of this layer and the green bodies above this layer is more than 97%;

[0097] When h1≥90%H is satisfied, the density of the ceramic sheet obtained by sintering the green body of this layer and the green bodies above this layer reaches more than 99%.

[0098] The beneficial effects of this application are:

[0099] 1) By further placing a smaller crucible inverted in the sintering crucible, the space where the lithium-based ceramic green body is located can be reduced as much as possible, the lithium atmosphere concentration can be increased, and the density of the ceramic sheet obtained by sintering the top layer or multiple layers of green bodies at normal pressure can reach 99%;

[0100] 2) By setting a smaller crucible upside down and adjusting the relationship between the height of the green body stack and the height of the smaller crucible, ceramic sintered bodies with different densities can be obtained to meet the needs of different scenarios.

[0101] ① The crucible uses magnesium oxide instead of conventional aluminum oxide to avoid the crucible's absorption of lithium atmosphere;

[0102] ②Through Figure 1 The arrangement shown (inverted small crucible + green compact stacking) can ensure that the internal lithium atmosphere concentration is high enough while reducing the internal pores caused by excessive lithium in the green compact itself, thereby improving the density.

[0103] ③ When stacked, the density increases as the green body is placed upwards. Therefore, increasing the total height h of the green body can further improve the overall density, especially for the top green body, because the lithium atmosphere concentration increases as the green body is placed upwards and is not affected by other factors. That is, by adjusting the relationship between the height of the green body stack and the height of the small crucible, a stepped density can be achieved, and the top layer or layers can reach a density of 99%.

[0104] The scheme of the present application is described below in conjunction with the following specific examples. Unless otherwise specified, the raw materials used in the following examples are all from common commercial products, and the devices or equipment used are all purchased from conventional market sales channels.

[0105] Preparation of LLZTO (LLTO-based ceramic doped with Ta) pre-sintered powder:

[0106] Ta2O5, Li2CO3, La2O3, ZrO2 according to Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 The materials are mixed in a proportion of the measured numbers, wherein Li2CO3 is in excess of 18%. After mixing, the materials are put into a ball mill according to the ratio of ball:material:water=2:1:1, the rotation speed is 500rpm, the ball milling time is 5h, and the ball milling is dried and crushed after ball milling. The crushed powder is placed in an Al2O3 crucible and sintered at 920℃ / 720min to obtain pre-burned powder.

[0107] Preparation of LLZTO granulated powder:

[0108] The LLZTO powder pre-burned at 920°C was mixed with water, with the solid content controlled at 35%. After mixing, it was poured into a sand mill with the sand mill parameters set to 2000rpm / 240min. After the slurry was taken out and fully stirred in a barrel to ensure that it was evenly dispersed, and then the spray granulation process was carried out, with the air inlet temperature set to 150°C and the air outlet temperature set to 75°C, to obtain LLZTO granulated powder in the target particle size range.

[0109] Example 1

[0110] (1) 15 g of large-particle (particle size range 0.5-5 mm) LLZTO pre-calcined powder is placed at the bottom of the large MgO crucible to provide Li volatilization in the crucible, and the large particles are convenient for cleaning after sintering. Fine LLZTO pre-calcined powder (particle size 20-80 μm) that has been ground and passed through a 200-mesh sieve is evenly spread on the upper layer of the large-particle pre-calcined powder;

[0111] (2) Take 5 g of LLZTO granulated powder obtained by spray granulation, press it into a φ30 mm green body at a pressure of 170 MPa, place it in the center on the pre-sintered powder and compact it.

[0112] (3) Arrange the green body, 2 g of fine LLZTO pre-sintered powder, and the green body upward and compact them to ensure that no two green bodies are in direct contact. A total of 12 ceramic green bodies are sintered, with the bottom layer being No. 1 and the top layer being No. 12.

[0113] (4) Cover the crucible with a smaller MgO crucible and the top MgO cover, place it in a box furnace, raise the temperature to 1100°C at 3-5°C / min under normal pressure and keep it for 5 hours for sintering.

[0114] In this embodiment, the total height of the 12 layers of green compacts is 45 mm, the height H of the smaller MgO crucible is 50 mm, and h / H=0.9;

[0115] In this embodiment, the thickness of the green body is about 3.5 mm, the height H of the smaller MgO crucible is 50 mm, 12 LLZTO green bodies are stacked, and fine LLZTO pre-burned powder is laid between the green bodies. After placement, the height h1 of the 4th green body from bottom to top is 15 mm, h1=0.3H, and the density of the 4th LLZTO ceramic sheet after sintering is 96.0%; the height h1 of the 10th green body from bottom to top is 37 mm, 0.9H>h1>0.7H, and the density of the 10th LLZTO ceramic sheet after sintering is 97.2%; the height h1 of the 12th green body (the uppermost green body) from bottom to top is 45 mm, h1=0.9H, and the density of the 12th LLZTO ceramic sheet after sintering is 99.0%.

[0116] Example 2

[0117] Similar to Example 1, the only difference is the number of green sheets stacked (i.e. the number of green sheets and the stacking height);

[0118] (1) 15 g of large-particle (particle size range 0.5-5 mm) LLZTO pre-calcined powder is placed at the bottom of the large MgO crucible to provide Li volatilization in the crucible, and the large particles are convenient for cleaning after sintering. Fine LLZTO pre-calcined powder (particle size 20-80 μm) that has been ground and passed through a 200-mesh sieve is evenly spread on the upper layer of the large-particle pre-calcined powder;

[0119] (2) Take 5 g of LLZTO granulated powder obtained by spray granulation, press it into a φ30 mm green body at a pressure of 170 MPa, place it in the center on the pre-sintered powder and compact it.

[0120] (3) Arrange the green body, 2 g of fine LLZTO pre-sintered powder, and the green body upward and compact them to ensure that no two green bodies are in direct contact. A total of 8 ceramic green bodies are sintered, of which the bottom layer is No. 1 and the top layer is No. 8.

[0121] (4) Cover the crucible with a smaller MgO crucible and the top MgO cover, place it in a box furnace, raise the temperature to 1100°C at 3-5°C / min under normal pressure and keep it for 5 hours for sintering.

[0122] In this embodiment, the total height h of the 8-layer green body is 31.5 mm, the height H of the smaller MgO crucible is 50 mm, and h / H=0.63;

[0123] The density of the LLZTO ceramic sheets obtained after sintering the green sheets of each number is shown in Table 1. In this embodiment, the thickness of the green sheet is about 3.5 mm, the height H of the smaller MgO crucible is 50 mm, and 8 LLZTO green sheets are stacked and placed, and fine pre-burned powder is spread between the green sheets. After placement, the height h1 of the 4th green sheet from bottom to top is 16 mm, 0.7H>h1>0.3H, and the density of the 4th LLZTO ceramic sheet after sintering is 96.01%. The height h1 of the 8th green sheet from bottom to top is 31.5 mm, 0.7H>h1>0.3H, and the density of the 8th LLZTO ceramic sheet after sintering is 96.88%.

[0124] Table 1

[0125]

[0126] Example 3

[0127] The schematic diagram of the device is as follows Figure 2 As shown, the number of green pieces placed is reduced from 12 to 4, and the rest is consistent with Example 1.

[0128] After stacking 4 green sheets, the total height h of the 4 layers of green sheets is 15 mm, h = 0.3H, and the height h1 of the 4th layer of green sheets is also 15 mm. After the 4th layer of green sheets is sintered, the density of the LLZTO ceramic sheet is as follows: Figure 4 As shown in , it is 95.7%.

[0129] Comparing Example 3 with Comparative Example 1, it can be seen that the density can be increased from about 94% to about 95% to 96% by sintering the green compacts in an inverted small crucible and stacking manner;

[0130] Comparing Example 3 with Example 1, it can be seen that when the total height h of the green body is low, the effect of the inverted small crucible on improving the density is limited. When the total height h of the green body is increased, the density of the green body can be significantly improved, especially for the top layer or layers of the green body.

[0131] Comparative Example 1

[0132] The schematic diagram of the device is as follows Figure 3 As shown, no smaller magnesium oxide crucible is added, and the rest is consistent with Example 1.

[0133] The density of the LLZTO ceramic sheets obtained in each layer in Example 1, Example 3 and Comparative Example 1 is as follows: Figure 4 As shown in the figure, it can be seen that the density of the LLZTO ceramic sheets of each layer in Example 1 gradually increases, and the maximum can reach 99%, indicating that the method provided in the present application can prepare high-density lithium-based ceramic sheets under normal pressure, and at the same time, lithium-based ceramic sheets of different densities can be obtained as needed.

[0134] By comparing Example 1 with Example 3, it can be seen that the density of the ceramic sheet obtained by sintering the fourth layer of green body in Example 1 is higher than that of the ceramic sheet obtained by sintering the fourth layer of green body in Example 3, which means that when the total height h of the green body is low, the effect of increasing the density by the inverted small crucible is limited. When the total height h of the green body is increased, the density of the LLZTO ceramic sheet obtained by sintering each layer of green body can be significantly improved, and the density shows an upward trend, and the maximum density can reach more than 99%.

[0135] Comparison of the embodiments with comparative example 1 shows that sintering the green compacts by inverting the small crucibles and stacking them can improve the density of the LLZTO ceramic sheets obtained by sintering, especially the density of the ceramic sheets obtained by sintering the top layers of green compacts.

[0136] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a lithium-based ceramic material, characterized in that: The following steps are involved: Step S1: stacking a plurality of lithium-based ceramic green sheets (1) in a thickness direction and placing them in a first crucible (3) with a first lithium-based ceramic pre-fired powder (2) on the bottom, wherein a second lithium-based ceramic pre-fired powder (4) is sprinkled between the plurality of lithium-based ceramic green sheets (1); Step S2: placing the second crucible (5) upside down into the first crucible (3) with its opening facing downward, so that the plurality of lithium-based ceramic green sheets are contained in the second crucible (5); Step S3: The first crucible (3) containing the second crucible (5) is sealed with a crucible cover (6) and then subjected to sintering treatment to sinter the lithium-based ceramic green body (1) to obtain the lithium-based ceramic material.

2. The method according to claim 1, characterized in that: The total height h of the plurality of lithium-based ceramic green sheets (1) stacked in the thickness direction and the height H of the second crucible (5) satisfy: 0.3H≤h<H; Preferably, 0.5H≤h<H; Further preferably, 0.7H≤h<H; Still more preferably, 0.9H≤h<H.

3. The method according to claim 1, characterized in that The total height h of the plurality of lithium-based ceramic green sheets (1) stacked in the thickness direction and the height H of the second crucible (5) satisfy: 0.5H≤h<H; and When the height h1 of a lithium-based ceramic green body after a plurality of lithium-based ceramic green bodies (1) are stacked satisfies 0.3H≤h1<0.7H, the density of the lithium-based ceramic material obtained by sintering the green body is 96%-97%; When the height h1 of a lithium-based ceramic green body after a plurality of lithium-based ceramic green bodies (1) are stacked satisfies 0.7H≤h1<0.9H, the density of the lithium-based ceramic material obtained by sintering the green body is 97% to 99%; When the height h1 of a lithium-based ceramic green body after a plurality of lithium-based ceramic green bodies (1) are stacked satisfies 0.9H≤h1<H, the density of the lithium-based ceramic material obtained by sintering the green body is greater than or equal to 99%; The height h1 is the distance between the upper surface of a lithium-based ceramic green body and the lower surface of the lowest lithium-based ceramic green body.

4. The method according to claim 1, characterized in that The particle size of the first lithium-based ceramic pre-fired powder (2) is 0.5 to 5 mm; the particle size of the second lithium-based ceramic pre-fired powder (4) is 20 to 80 μm.

5. The method according to any one of claims 1 to 4, characterized in that: The step S1 further comprises: after laying a layer of second lithium-based ceramic pre-fired powder (4) on the first lithium-based ceramic pre-fired powder (2), a plurality of lithium-based ceramic green sheets (1) are stacked along the thickness direction and placed on the second lithium-based ceramic pre-fired powder (4).

6. The method according to claim 1, characterized in that The first crucible (3), the second crucible (5) and the crucible cover (6) are all made of magnesium oxide.

7. The method according to claim 1, characterized in that The first lithium-based ceramic pre-fired powder and the second lithium-based ceramic pre-fired powder are independently obtained by the following methods: Providing raw materials according to the stoichiometric ratio of each element in the lithium-based ceramic material, wherein the raw materials include a lithium source, the mass of the lithium element in the lithium source is recorded as m, and the theoretical amount of the lithium element is recorded as m0, satisfying 1.1m0≤m≤1.2m0; The raw materials are then pre-sintered at 800-1000° C. and crushed to obtain lithium-based ceramic pre-sintered powder.

8. The method according to claim 1, characterized in that The lithium-based ceramic green body is obtained by the following method: Providing raw materials according to the stoichiometric ratio of each element in the lithium-based ceramic material, wherein the raw materials include a lithium source, the mass of the lithium element in the lithium source is recorded as m, and the theoretical amount of the lithium element is recorded as m0, satisfying 1.1m0≤m≤1.2m0; The raw materials are then pre-sintered at 800-1000° C. and crushed to obtain lithium-based ceramic pre-sintered powder; Then, the lithium-based ceramic pre-sintered powder is granulated and formed to obtain the lithium-based ceramic green body.

9. The method according to claim 1, characterized in that: The lithium-based ceramic material is selected from any one of the substances shown in Formula 1; Li 7-x La3Zr 2-x M x O 12 Formula 1 Wherein, M is a doping element, and M is selected from at least one of Ta, Nb, W, and Ti; The value range of x is: 0≤x≤1.

0.

10. A lithium-based ceramic material, characterized in that: Prepared according to the method according to any one of claims 1 to 9; Preferably, the density of the lithium-based ceramic material is above 96%; Further preferably, the density of the lithium-based ceramic material is above 97%; Still more preferably, the density of the lithium-based ceramic material is above 99%.

Citation Information

Patent Citations

  • Sintering method for lead-containing piezoelectric ceramic product

    CN112194464A

  • Preparation method and application of garnet type solid electrolyte

    CN115275329A

  • PZT-based piezoelectric ceramic solid-phase sintering process optimization method

    CN116813336A

  • Lead-based piezoelectric ceramic and preparation method thereof

    CN117510198A

  • Method for inhibiting alkali metal volatilization during niobate base lead-free piezoelectric ceramic sintering process

    CN1935745A

Cited By

  • Method for preparing lithium-based ceramic body particles by using lithium-containing molten compound and lithium-based ceramic body particles

    CN120535310A